International encyclopedia of dance : a project of Dance Perspect ives Foundation, Inc. - Cohen, Selma Jeanne, 1920-2005.; Dance Perspectives Foundation (New York : Oxford University Press, 1998)
"Exciting and fascinating, this reference work succeeds in its goal of bringing "joy as well as enlightenment" about all forms of dance in all countries of the world. An extremely useful synoptic outline of con tents" with nine sections (including "Ritual and Religion" and "Popular Entertainment") enables the user to explore dance in its cultural and social aspects, while topical essays complement the 2,000-plus entries. Heavily illustrated with black-and-white photographs, the encyclopedia captures the fluid movement of dance; with its depth and scope, this o utstanding work has carved a well-deserved niche".--"Outstanding Refere nce Sources : the 1999 Selection of New Titles", American Libraries, Ma y 1999. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references and index.
Keywords: Dance -- Encyclopedias; Ballet -- Encyclopedias